DOI: 10.4018/978-1-4666-9616-7.ch009
|View full text |Cite
|
Sign up to set email alerts
|

STEM Learning in Middle Grades by Technology-Mediated Integration of Science and Mathematics

Abstract: In an attempt to foster inquiry-oriented learning in middle grades (grades 6 – 8), a technology mediated pedagogy integrating science and mathematics was promoted through Project SMILE (Science and Mathematics Integration for Literacy Enhancement). It involved in-service teachers in professional learning and classroom implementation over a period of two academic years, with the explicit goal of enhancing teachers' ability to foster more authentic inquiry in their classes. This chapter describes the design of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similarly to other researchers (e.g. Dass, & Spagnolo, 2016), we found that use of a technological tool like InspireData, can set mathematical content in real world contexts that can help students experience mathematics and statistics in the way envisioned by the CCSS-M. All children in our study were able to raise original questions and to use InspireData © to seek answers to these questions by analyzing data in multiple ways that would be difficult otherwise. Moreover, there are strong indications in our study to support the belief that utilization of the affordances provided by a dynamic statistics software such as InspireData © , can indeed scaffold and extend children's informal stochastic reasoning (Ben-Zvi, 2006) by encouraging them to build, refine, and reorganize their intuitive understandings about statistics.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly to other researchers (e.g. Dass, & Spagnolo, 2016), we found that use of a technological tool like InspireData, can set mathematical content in real world contexts that can help students experience mathematics and statistics in the way envisioned by the CCSS-M. All children in our study were able to raise original questions and to use InspireData © to seek answers to these questions by analyzing data in multiple ways that would be difficult otherwise. Moreover, there are strong indications in our study to support the belief that utilization of the affordances provided by a dynamic statistics software such as InspireData © , can indeed scaffold and extend children's informal stochastic reasoning (Ben-Zvi, 2006) by encouraging them to build, refine, and reorganize their intuitive understandings about statistics.…”
Section: Discussionsupporting
confidence: 73%
“…In STEM education, one of the preferred learning models among teachers is the 5E (Dass, 2015). Bybee (2015) claims that the model is excellent for teaching 21st-century skills and STEM subjects.…”
Section: Stem-based 5e Model Module (Stem-5e)mentioning
confidence: 99%
“…Research in the application of the approach STEM in Learning Cycle 5E has not done much in my country. But there are some foreign researchers have conducted Past studies showed that the application of the approach STEM in Learning Cycle 5E improved learning outcomes, liveliness and creativity of students : (1) Dona Clem [10] did research 5E Model Use For elementary STEM Education on the concept of pendulum swings, the result is an increase in students' creativity; (2) Sevil Ceylan [11] researched Improving A Sample Lesson Plan For Secondary Within The STEM (By Model 5E) on Chemistry subject matter, result there was an increased level of understanding of the concept of the student; (3) Pradeep M Dass [12] did STEM Teaching Effectively With The Learning Cycle Approach to the concept of Population Growth (Biology), the results Students are an increased level of understanding of the concept. The purpose of this study is to identify whether there are significant differences concept understanding inprovement between students who received LC 5E combined with STEM higher than students who had learning LC 5E without STEM…”
Section: Relevant Researchmentioning
confidence: 99%